Indignation - Roth, Phillip (Jonathan Cape, 2008)
What impact can American history have on the life of the vulnerable individual? It is 1951 in America, the second year of the Korean War. A studious, law-abiding, intense youngster from Newark, New Jersey, Marcus Messner, is beginning his sophomore year on the pastoral, conservative campus of Ohio?s Winesburg College. And why is he there and not at the local college in Newark where he originally enrolled? Because his father, the sturdy, hard-working neighborhood butcher, seems to have gone mad--mad with fear and apprehension of the dangers of adult life, the dangers of the world, the dangers he sees in every corner for his beloved boy. As the long-suffering, desperately harassed mother tells her son, the father?s fear arises from love and pride. Perhaps, but it produces too much anger in Marcus for him to endure living with his parents any longer. He leaves them and, far from Newark, in the midwestern college, has to find his way amid the customs and constrictions of another American world.--From publisher?s description.